Severe spinal cord hypoplasia due to a novel ATAD3A compound heterozygous deletion - Tomohiro Ebihara; Taro Nagatomo; Yohei Sugiyama; Tomoko Tsuruoka; Yoshiteru Osone; Masaru Shimura; Makiko Tajika; Keiko Ichimoto; Yuki Naruke; Nana Akiyama; Sze Chern Lim; Yukiko Yatsuka; et al. (Molecular Genetics and Metabolism Reports, 2022)
Biallelic deletions extending into the ATPase family AAA-domain containing protein 3A (ATAD3A) gene lead to infantile lethality with severe pontocerebellar hypoplasia (PCH). However, only 12 such cases have been reported worldwide to date, and the genotype–phenotype correlations are not well understood. We describe cases associated with the same novel biallelic deletions of the ATAD3A and ATAD3B/3A regions in Japanese siblings with severe spinal cord hypoplasia and multiple malformations, including PCH, leading to neonatal death. The ATAD3A protein is essential for normal interaction between mitochondria and endoplasmic reticulum and is important for mitochondrial biosynthesis. The cases were evaluated using whole-genome sequencing for genetic diagnosis of mitochondrial disease. Spinal cord lesions associated with biallelic compound heterozygous deletion extending into the ATAD3A gene have not been reported. In addition, the ATAD3A deletion was 19 base pairs long, which is short compared with those reported previously. This deletion introduced a frameshift, resulting in a premature termination codon, and was expected to be a null allele. The pathological findings of the atrophic spinal cord showed gliosis and tissue destruction of the gray and white matter. We describe spinal cord lesions as a new central nervous system phenotype associated with a biallelic compound heterozygous deletion extending into the ATAD3A gene. Biallelic ATAD3A deletions should be considered in cases of mitochondrial disease with spinal cord hypoplasia and PCH.